The Impact of Current Ratio, Total Asset Turnover, Debt-Equity Ratio, Return on Equity, And Price Earning Ratio Toward Stock Return - Muslikin Muslikin; Rahmad Afrenal Alim (Universitas Mercu Buana, 2023)
This study aims to examine the effect of Current ratio (CR), Total asset turnover (TATO), Debt equity ratio (DER), Return on equity (ROE), and Price earning ratio (PER) on stock returns in pharmaceutical sub-sector companies listed in Indonesia Stock Exchange (IDX). The population of this research is 10 pharmaceutical companies that publish annual reports on the websites of each company in 2015 – 2020 and the sampling method of pharmaceutical companies use the purposive sampling method and based on predetermined criteria, a sample of 7 companies is obtained. In this study, the analytical method used is the panel data regression analysis method. The results showed that the Current ratio (CR), Total asset turnover (TATO) and Debt equity ratio (DER) had no effect while Return on equity (ROE) and Price earning ratio (PER had an effect on Stock Return in Pharmaceutical Sub-Sector Companies listed in IDX Period 2015 – 2020.